2017
DOI: 10.17503/agrivita.v39i3.937
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Cowpea Genotypes to Arbuscular Mycorrhiza

Abstract: A pot experiment was conducted under glasshouse conditions to evaluate response of some cowpea genotypes to Arbuscular Mycorrhiza. It was a 2 x 6 factorial experiment comprising factors of mycorrhizal inoculation (M) with AM fungal inoculum (M 1 ) and without AM fungal inoculum (M 0 ), and of plant genotypes (G) with G f (a cowpea inbred line), G m (a mung bean inbred line), G h1, G h2 , G h3 and G h4 (the 1 st , 2 sd , 3 rd and 4 th generation of cowpea hybrids, derived from cross-breeding G f x G m as female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…The numbers followed by the same letters on the mean of treatment and control were not significantly different in the 5% contrast test (+) / (-): interaction types and inoculums significant or not significant. The response of plant growth to AMF varies for each type of plant (Rohyadi et al, 2017;Setyaningsih et al, 2018;Begum et al, 2019). Some results of this study are different from those previous study by Suharno et al (2017) and Wilujeng et al (2020) on maize.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The numbers followed by the same letters on the mean of treatment and control were not significantly different in the 5% contrast test (+) / (-): interaction types and inoculums significant or not significant. The response of plant growth to AMF varies for each type of plant (Rohyadi et al, 2017;Setyaningsih et al, 2018;Begum et al, 2019). Some results of this study are different from those previous study by Suharno et al (2017) and Wilujeng et al (2020) on maize.…”
Section: Resultscontrasting
confidence: 99%
“…AMF response in enhancing the growth of plants is very diverse. Most AMFs can significantly increase plant growth, but some do not have a significant effect (Tarbell and Koske, 2007;Bücking et al, 2012;Rohyadi et al, 2017). Positive responses often occur when the treatment of plant growth is done on the land or media, which is lacking phosphorus (Tarbell and Koske, 2007) and marginal land (Suharno et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, findings point towards non-random association patterns in plant-AM fungal identities [ 7 ], and the wide functional diversity exhibited by fungal taxa [ 8 ] highlights the importance of the knowledge of plant-fungal partner identity when optimizing agricultural production systems. Furthermore, it has been shown that different varieties of the same crop can respond differently to the same AM fungal isolates [ 9 , 10 ]. Other authors have found differences in the composition of AM fungal communities associated with different varieties, even when initially exposed to the same AM fungal community.…”
Section: Introductionmentioning
confidence: 99%